Colchicine in COVID-19: an Old Drug, New Use - Schlesinger, Naomi (Curr Pharmacol Rep, 2020)
PURPOSE OF REVIEW: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection, is a pandemic causing havoc globally. Currently, there are no Food and Drug Administration (FDA)-approved drugs to treat COVID-19. In the absence of effective treatment, off-label drug use, in lieu of evidence from published randomized, double-blind, placebo-controlled clinical trials, is common in COVID-19. Although it is vital to treat affected patients with antiviral drugs, there is a knowledge gap regarding the use of anti-inflammatory drugs in these patients. RECENT FINDINGS: Colchicine trials to combat inflammation in COVID-19 patients have not received much attention. We await the results of ongoing colchicine randomized controlled trials in COVID-19, evaluating colchicine’s efficacy in treating COVID-19. SUMMARY: This review gives a spotlight on colchicine’s anti-inflammatory and antiviral properties and why colchicine may help fight COVID-19. This review summarizes colchicine’s mechanism of action via the tubulin-colchicine complex. Furthermore, it discussed how colchicine interferes with several inflammatory pathways, including inhibition of neutrophil chemotaxis, adhesion, and mobilization; disruption of superoxide production, inflammasome inhibition, and tumor necrosis factor reduction; and its possible antiviral properties. In addition, colchicine dosing and pharmacokinetics, as well as drug interactions and how they relate to ongoing, colchicine in COVID-19 clinical trials, are examined.